'It's a huge maze, the system, it's a terrible maze': Dementia carers' constructions of navigating health and social care services. (September 2014) - Peel, Elizabeth; Harding, Rosie
Dementia is a challenging, progressive set of conditions which present a large care burden to informal, familial carers. A complex array of health and social care services are needed to support people living with dementia. Drawing on the interlinked 'Duties to Care' and 'Dementia Talking' projects, in this article we focus on British carers' talk about health and social care services. We explore data from a mixed-method questionnaire ( n  = 185), four focus groups and eleven interviews with informal carers of people living with dementia using thematic discourse analysis. Three themes are discussed: (1) services as a 'maze'; (2) services as overly limited – 'beyond our remit'; and (3) the battle and fighting discourse deployed by these carers. Our analysis highlights that carers find navigating systemic issues in dementia care time-consuming, unpredictable and often more difficult than the caring work they undertake.